The Effect of Sintering Temperature on Hydrophobic Characteristic of Silica Manganese /Polystyrene (SiMn/PS) Nanocomposite - Dian Septiana; - Ratnawulan (Department of Physics – Universitas Negeri Padang UNP, 2021)
Currently a lot of research has been done on hydrophobic layers, but in its application the layer is easily damaged and is not corrosion resistant. Therefore, this research intends to decide the effect of variations insintering temperature on the hydrophobic characteristic of SiMn/PS nanocomposite layers using a sintering temperature of 60oC,100oC,140oC,180oC and 200oC for 1 hour using a furnace.This research was conducted in the Material Physics Laboratoryof0theFacultyof0Mathematics and Natural Sciences and the Chemistry Laboratory of0th eFaculty of0Mathematics and Natural Sciences,Padang State University.This research uses HEM-3D (High Energy Milling Ellipse-3D Mention), XRD(X-RayDifraction) and0SEM (ScanningElectron Microscope) tools. The precursor was made by giving 0.5 grams of polystyrene, 0.2 grams of silica powder and 0.2 grams of manganese powder. Coating is done by spin coating method. The results of this research from the variation of the sintering temperature showed that the SiMn/PS nanocomposite layer was hydrophobic based on the contact angle test.The highest contact angle is at a temperature of 600C.Currently a lot of research has been done on hydrophobic layers, but in its application the layer is easily damaged and is not corrosion resistant. Therefore, this research intends to decide the effect of variations in sintering temperature on the hydrophobic characteristic of SiMn/PS nanocomposite layers using a sintering temperature of 60oC, 100oC, 140oC, 180oC and 200oC for 1 hour using a furnace. This research was conducted in the Material Physics Laboratory0of0the0Faculty0of0Mathematics0and0Natural0Sciences and the Chemistry Laboratory0of0the0Faculty0of0Mathematics0and0Natural0Sciences, 0Padang0State0University.This research uses HEM-3D (High Energy Milling Ellipse-3D Mention), XRD0 (X-Ray0Difraction) 0and0SEM0(Scanning Electron Microscope) tools. The precursor was made by giving 0.5 grams of polystyrene, 0.2 grams of silica powder and 0.2 grams of manganese powder. Coating is done by spin coating method. The results of this research from the variation of the sintering temperature showed that the SiMn/PS nanocomposite layer was hydrophobic based on the contact angle test. The highest contact angle is at a temperature of 600C.